Partisan Wedding : Stories - Viganò, Renata, 1900-1976 (Book collections on Project MUSE., 1999)
World War II stories on Italian women in the Resistance as heroines and traitors, and the way they exploited their femininity. In Red Flag, a woman hides guns by covering them with a soiled sanitary napkin.